Calculating the Biocapacity of the Saugeen Ojibway Nation Claims of Title and Treaty - Kish, Kate; Pal, Kaitlin (Journal of Aboriginal Economic Development)

(untitled) (CANDO, 2025)
This paper explores a land claim case initiated by the Saugeen Ojibway Nation (SON) concerning their traditional territory in Ontario, integrating the principles of the two-eyed seeing approach by bringing the Ecological Footprint and Biocapacity (EFB) methodology into the case as support alongside cultural and Indigenous views. EFB is an environmental indicator used to understand the amount of Earth’s resources an area can provide to support human activities. Using geomatics and EFB research, we quantify the regenerative capacity and environmental significance of SON’s territory. The analysis reveals that cropland, distinguished by Ontario’s high yield factor and fertile soil, possesses the highest Biocapacity within the region, indicating its potential to sustain Indigenous livelihoods. The calculated Biocapacity of SON’s traditional territory underscores its ability to support a population of 594,572 people, emphasizing the vast number of ecological resources available within the territory. We look at the juxtaposition of Indigenous knowledge with scientific analysis within this case and how it can help support Indigenous land claims cases. Through this interdisciplinary approach, the paper contributes to the broader discourse on Indigenous land rights and environmental stewardship, advocating for the recognition and preservation of the ecological heritage of Indigenous lands within the framework of the two-eyed seeing approach.